2017
DOI: 10.1155/2017/9160504
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sedentary Behaviour and Physical, Cognitive, and Psychosocial Status among Older Adults in Assisted Living

Abstract: Objective Identification of the factors that influence sedentary behaviour in older adults is important for the design of appropriate intervention strategies. In this study, we determined the prevalence of sedentary behaviour and its association with physical, cognitive, and psychosocial status among older adults residing in Assisted Living (AL). Methods Participants (n = 114, mean age = 86.7) from AL sites in British Columbia wore waist-mounted activity monitors for 7 consecutive days, after being assessed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 33 publications
2
52
1
Order By: Relevance
“…However, studies indicate that exacerbated exposure to sedentary behaviour—activities performed in a sitting/reclining position that do not substantially increase energy expenditure above resting values ≤1.5 METs [9]—are associated with a higher propensity to adverse health factors [10,11,12], even in sufficiently active individuals [13]. …”
Section: Introductionmentioning
confidence: 99%
“…However, studies indicate that exacerbated exposure to sedentary behaviour—activities performed in a sitting/reclining position that do not substantially increase energy expenditure above resting values ≤1.5 METs [9]—are associated with a higher propensity to adverse health factors [10,11,12], even in sufficiently active individuals [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Overall, sedentary behaviour was significantly associated with at least one measure of physical function in 17 of 28 studies (60%; see Figure 2.6). Associations were more likely observed in clinical populations (5 out of 7 studies; 71%) 81,106,[111][112][113] compared with community-dwelling samples (11 out of 21 studies; 52%). 101,102,109,110,117,118,[122][123][124]126,128 All seven longitudinal studies found a detrimental association of sedentary time with physical function; i.e., more sedentary time was associated with poorer physical function.…”
Section: Overall Findingsmentioning
confidence: 97%
“…There is consistent evidence of an association of sedentary behaviour with overall performancebased physical function, with all seven studies reporting a deleterious association. 102,105,111,112,[122][123][124] In the Rosenberg et al (2016) study, significant associations were only observed when objectively assessed sedentary time was used; other associations were non-significant.…”
Section: Association Of Sedentary Behaviour With Overall Performance-mentioning
confidence: 99%
See 2 more Smart Citations